Various Shallot Seed Treatments with Trichoderma to Increase Growth and Yield on Sandy Coastal - Stefany Darsan; Endang Sulistyaningsih; Arif Wibowo (Jurnal Ilmu Pertanian, 2016)
Sandy coastal area is a poor land, with minimal nutrients and low ability to store water and nutrition. Therefore, plant is difficult to grow well, consequently the treatments for improving sandy coastal is required before planting to support their growth. Application of Trichoderma as a plant-growth promoting and controlling pathogens had been known. Shallot seed treatment by Trichoderma agents was intended to improve and support plant growth and yield in the sandy coastal land. The aim of experiment was to determine the most effective treatment to improve growth and yield of shallot on sandy coastal land. The experiment had been carried out in Yogyakarta during August - November 2015. The factorial treatments of cultivar and Trichoderma applications were arranged in Completely Randomized Design with three replications. The shallot cultivars consisted of Tiron, Crok, and Biru, while Trichoderma application consisted of control (no treatment), sprayed with Trichoderma, soaked in Trichoderma, matricontioning media i.e. rice husk charcoal and brick in combination with Trichoderma. The collected data related to plant growth and yield. The result showed that seed treatment methods with Trichoderma increased the plant height, the leaf area index, extensive root, net assimilation rate (NAR), plant growth rate (PGR), Nitrate Reductase Activities (NRA), total chlorophyll, and fresh bulb weight. The best technical treatment for cultivar Tiron was soaked with Trichoderma, and Crok was sprayed with Trichoderma, while Biru cultivar was using brick in combination with Trichoderma.